Sosialisasi QRIS sebagai Upaya Peningkatan Literasi Keuangan dan Pendapatan UMKM melalui Program KKN di Kawasan Eks Lokalisasi Bandar Baru - Simanungkalit, Cici El Dirrah Syafitri; Salsabila, Divia Inge; Ramadhan, Irfan Aqil; Azizah, Nur Wafiq; Sembiring, Rifky Bas Praptama; Ramadi, Bagus (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement program focuses on the socialization of Quick Response Code Indonesian Standard (QRIS) as a strategy to enhance financial literacy and income among Micro, Small, and Medium Enterprises (MSMEs) in the ex-localization area of Bandar Baru, Sibolangit. The program was conducted as part of the Community Service (KKN) of Universitas Islam Negeri Sumatera Utara. The methods applied include observation, structured interviews, and direct mentoring to MSMEs, particularly in introducing QRIS as a digital payment system. The socialization activities emphasized the importance of digital financial literacy, practical training on QRIS usage, and awareness of consumer protection through the PEKA (Peduli, Kenali, Adukan) program. The findings revealed that prior to the program, only 13.3% of MSMEs had used QRIS, while after the intervention, 50% expressed interest and began registering for QRIS. Furthermore, participants demonstrated increased understanding of QRIS functions, technical skills in digital transactions, and more positive attitudes toward cashless payments. Although challenges remained, such as limited access to digital devices and weak internet connectivity, the program successfully promoted behavioral changes and provided new insights into digital finance. The results indicate that socialization through KKN is effective in improving financial literacy and encouraging digital transformation for MSMEs in rural communities.